The water reform in Burkina Faso between discourse and reality: the case of water user associations in Bougouriba water basin in SW [South West region] Burkina Faso [Abstract only] - Debevec, Liza; Banhoro, Yacouba (2014)
For two decades now Burkina Faso has been trying to adopt the global concept of IWRM. The official texts were developed between 1996 and 2001, while the experiment was being put into action in the Nakambe river basin. Following a positive outcome, the Action plan on integrated water resource management was adopted in 2003, defining a strategy and action plan to be executed by the water resource management by the 2015 deadline. We try to understand the effects of the reform at the grass roots level, how it has been taken and understood by the local population in the South West region of Burkina Faso, which happens to be one of the most fertile and wet areas of the country, but paradoxically also a region facing problems in WRM and in having access to drinking water. Our research suggests that the reform is definitely in progress in the area of study and that it has created a sense of hope and expectations among the local population with regard to effective management solutions as to the availability and supply of drinking water. However, a gap still exists between the legal texts of the reform and their application in the field and lies at the level of the appropriation of the concept of IWRM, the availability of financial resources and the required technical skills.